1995
DOI: 10.2307/2445615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reproductive Mode on Demography and Life History in Arabis fecunda (Brassicaceae)

Abstract: Life history theory predicts that trade-offs between growth and reproduction should be dictated by a population's mortality schedule. We tested this prediction with Arabis fecunda, a short-lived perennial that occurs in many different habitats in southwest Montana. Individuals produce either or both axillary or terminal inflorescences. Axillary-flowering plants are usually iteroparous and have smaller reproductive bouts, while terminal-flowering plants have larger reproductive bouts, and tend to be semelparous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…However, because the root stock diameter, and thus the stored photosynthate in roots and rosette leaves, is greater for naturally browsed plants, recovery of lost tissue may be easier for those plants. There is a tradeoff between allocating resources to growth or reproduction (Biere 1995;Lesica and Shelly 1995;Reekie 1997) and our results indicate that clipped and naturally browsed plants are allocating resources towards the production of biomass in lieu of seeds. Despite their larger size, fruit and seed production of naturally browsed plants seed did not exceed that of control plants.…”
Section: Discussionmentioning
confidence: 72%
“…However, because the root stock diameter, and thus the stored photosynthate in roots and rosette leaves, is greater for naturally browsed plants, recovery of lost tissue may be easier for those plants. There is a tradeoff between allocating resources to growth or reproduction (Biere 1995;Lesica and Shelly 1995;Reekie 1997) and our results indicate that clipped and naturally browsed plants are allocating resources towards the production of biomass in lieu of seeds. Despite their larger size, fruit and seed production of naturally browsed plants seed did not exceed that of control plants.…”
Section: Discussionmentioning
confidence: 72%
“…According to the classification of Grime (1979), Sarcocapnos species should be considered an S type of strategy, adapted to live in habitats of scarce or nil perturbation but highly tolerant to the stresses resulting from developing in cracks where the substrate, water, and nutrients are severely limited. Life-history theory predicts that environments where adult mortality is high and (or) highly variable encourage early maturation and high initial fecundity (Wilbur et al 1974;Young 1981;Stearns 1992), leading to shorter generation times and faster population growth rates (Lesica and Shelly 1995). However, characteristics of S. enneaphylla, such as a short life-span, early sexual maturity, and high seedling production, are found in species with a predominantly r-type strategy (Hutchings 1989), that is, species that are adapted to environments with a certain degree of periodic perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix projections assume fixed transition probabilities between population stages through time (Menges 1990). In addition, this assumes density-independent population growth and, thus, does not accurately project the long-term population future (Lesica and Shelly 1995). Nevertheless, this approach can be used to summarize short-term population dynamics and to compare the dynamics of different populations (Caswell 1989).…”
Section: Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though few studies have gathered data over more than three years (for exceptions see Meagher 1982, Pinero et al 1984, Enright and Watson 1991, 1992, Waite and Hutchings 1991, Bengtsson 1993, Svensson et al 1993, Horvitz and Schemske 1995, Lesica and Shelly 1995, Oostermeijer et al 1996, those that did have typically revealed more temporal variation in vital rates than have studies of shorter duration (Enright and Watson 1991). Though few studies have gathered data over more than three years (for exceptions see Meagher 1982, Pinero et al 1984, Enright and Watson 1991, 1992, Waite and Hutchings 1991, Bengtsson 1993, Svensson et al 1993, Horvitz and Schemske 1995, Lesica and Shelly 1995, Oostermeijer et al 1996, those that did have typically revealed more temporal variation in vital rates than have studies of shorter duration (Enright and Watson 1991).…”
Section: Discussionmentioning
confidence: 99%